The Rise of Service Employment in the Canadian Economy - Magun, Sunder (Relations industrielles / Industrial Relations, 1982)
This paper analyzes the trends in employment shares by industry and presents an employment profile of the service-producing and goods-producing sectors and examines some of the reasons for the shift to service jobs.